Pengelompokan Kabupaten/Kota Di Jawa Tengah Menurut Indeks Kerawanan Sosial Terhadap Demam Berdarah Dengue - Muzakky, A. Naufal; Budiarti, Winih (Politeknik Statistika STIS, 2024)
The high mortality rate of DHF in Central Java requires the government to reduce the burden of DHF disease by reducing community vulnerability or social vulnerability to DHF. Social vulnerability is a multidimensional concept that can be measured using a composite index. This index is useful for determining policy priority areas and dimensions. Therefore, the objectives of this study were to develop a Social Vulnerability Index to DHF (IKS DBD) using factor analysis, group districts/cities based on IKS DBD, and identify policy priority dimensions. The results showed that there are four factors that compose the IKS DBD, namely socioeconomic and urban, health services, vulnerable populations, and housing. The grouping of districts/cities resulted in five categories of vulnerability, namely very high, high, medium, low, and very low vulnerability. From the resulting radar plot, each group has different policy priority dimensions that can help the government in determining policies with significant impact.